The Jewish symbols = Symbole żydowskie - Łoziński, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In every culture, people have always used symbols giving them sense and assigning them a specific meaning. Over the centuries, with the passage of time religious symbols have mingled with secular symbols. The charisms of Judaism have mutually intermingled with the Christian ones taking on a new tribal or national form with influences of their own culture.
Keywords: Jews; Judaism; symbol; archetype; Judaica; Żydzi; judaizm; archetyp; judaica